2014
DOI: 10.1021/es500596a
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Transformation and Photoinduced Toxicity Reduction of Silver Nanoparticles in the Presence of Perfluorocarboxylic Acids under UV Irradiation

Abstract: The impact of perfluorocarboxylic acids (PFCAs) with carbon chain length C2 to C8 on the dissolution, aggregation, reactive oxygen species (ROS) generation, and toxicity of citrate-coated AgNPs was investigated under UV irradiation. The presence of PFCAs decreased dissolution, aggregation, ROS generation, and toxicity of AgNPs because the negatively charged PFCAs sorbed on AgNP surface enhanced their stability. Both dissolution and aggregation rate of AgNPs decreased with chain length of PFCAs under UV irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…It is also reported that the physicochemical properties of AgNPs are influenced by light since AgNPs are photo sensitive. Earlier studies suggested that fragmentation of AgNPs occurs via photoejection of electrons, which accelerates the release of ionic silver. , Furthermore, organic coatings (such as citrate) on the surface of AgNPs may oxidize on irradiation with resultant formation of electrons which may reduce any silver ions present to form Ag(0) which would then be expected to coalesce to form new AgNPs. Alternatively, these electrons may be stored by AgNPs thereby enhancing the reactivity of AgNPs. , …”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that the physicochemical properties of AgNPs are influenced by light since AgNPs are photo sensitive. Earlier studies suggested that fragmentation of AgNPs occurs via photoejection of electrons, which accelerates the release of ionic silver. , Furthermore, organic coatings (such as citrate) on the surface of AgNPs may oxidize on irradiation with resultant formation of electrons which may reduce any silver ions present to form Ag(0) which would then be expected to coalesce to form new AgNPs. Alternatively, these electrons may be stored by AgNPs thereby enhancing the reactivity of AgNPs. , …”
Section: Introductionmentioning
confidence: 99%
“…Because many micro-pollutants are very reactive with HO and/or SO À 4 , these processes have been widely used to oxidize organic pollutants, such as ATZ (Li et al, 2014;He et al, 2013;Liu et al, 2013). For instance, Khan et al (2013) studied ATZ degradation by UV/H 2 O 2 /Fe 2þ , UV=S 2 O 2À 8 =Fe 2þ , and UV=HSO À 5 =Fe 2þ .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the cell 757 damage caused by nanosilver to several organisms, such as E. coli, C. elegans, Raphidocelis 758 subcapitata, Chydorus sphaericus, Danio rerio, and Daphnia magna, could be alleviated by fulvic acids (FA), HA, and/or dissolved organic matter (DOM) because these organic substances can inhibit silver ion release (Cupi et al 2015, Seitz et al 2015, Yang et al 2014b. In addition, one study showed that under UV irradiation, perfluorocarboxylic acids (PFCAs) could significantly decrease nanosilver dissolution rate (as well as its aggregation and ROS generation) and hence reduce its toxicity to E. coli (Li et al 2014). Similarly, alginate could even mute the toxicity of nanosilver towards N. europaea by binding to (or covering) the nanosilver surface and blocking its dissolution (Ostermeyer et al 2013).…”
mentioning
confidence: 99%